Factors Affecting Domestic Tourists’ Satisfaction in Hikkaduwa, Sri Lanka - Samaraweera, K.G.; Ananda, T.G.Y.U. (NSBM Green University, 2019)
Tourism is one of the enormous and emerging sectors in the world economy which contributes about 10% to the global gross domestic product. The progress and the instigation are inevitably determined by the level of satisfaction of the tourists in a destination. As an island, Sri Lanka has great opportunities to promote tourism. Hikkaduwa is one of the eye catching areas which can mesmerize both international and domestic tourists. Sri Lankan tourism industry is in a backward position in promoting domestic tourism and only few studies had been conducted to measure the domestic tourists’ satisfaction in Sri Lanka. Under this backdrop, it is prudent to answer what are the factors which maximize the Western province tourists’ satisfaction in Hikkaduwa, Sri Lanka. The general objective of this study is to identify the Western province domestic tourists’ perception towards the satisfaction gained from Hikkaduwa as a tourist destination. Furthermore, the study attempts to investigate the relevance of 5A’s concept on domestic tourists’ satisfaction. The operational methodology for this study is a factor analysis which has three stages. First stage is the Exploratory Factor Analysis to identify the major factors that influence the domestic tourists’ satisfaction in Hikkaduwa. Second stage is the Confirmatory Factor Analysis to confirm the identified major factors from the Exploratory Factor Analysis. Finally, the Structural Equation Model to identify the relationships between the identified factors in the model. The Descriptive analysis of collected results has shown that majority of the Western province domestic tourists have prior experience in Hikkaduwa. According to the Factor analysis, the study found that Accommodation, Amenities, Attractions, Accessibility and Activities influence the domestic tourists’ satisfaction. Moreover, the study revealed that Accommodation, Amenities, Attractions, Accessibility and Activities have a significantly positive impact on domestic tourists’ satisfaction in Hikkaduwa. However, the activities impact 95% on domestic tourists’ satisfaction and it is the most crucial factor. Finally, this study suggests to introduce low budget tour packages, publication of an accommodation guide and tourist guide map in native languages and maintain the quality of the accommodations. Additionally, improving activities in the destination would help the stakeholders to increase the satisfaction level and the future growth of the domestic tourism industry in Hikkaduwa.
Keywords: Domestic Tourism; Tourists’ Satisfaction; 5A’s; Factor Analysis